Atração e retenção de talentos em empresas de engenharia consultiva no setor de petróleo e gás natural da cidade de Natal - Barreto, Cásio Carlos Pereira (2008)
This study addresses the question of attraction and retention of talent in companies that produce engineering projects in the area of oil and natural gas in the city of Natal. The objectives were to identify the mechanisms that these companies use to attract and retain talented professionals and what the relationship between these practices and performance of these organizations in the market. This is a case study of a qualitative nature which were included in the fullness of companies that work in that class in the capital Potiguar. Have been applied to the managers of these companies structured questionnaires with eleven issues orientativas based on theoretical reference adopted. The research finds that managers understand the word "talent", recognize the importance of the appreciation of its employees and the development of their innate abilities to better organizational performance, much due to the fact they are acting in a market of fierce competition. His companies - though not submit the formal procedures related to the subject in question - have mechanisms that can be characterized as the attraction and retention of talent. The relationships identified in this study are consistent with the results found in other studies and put the information here can serve as the basis for that other managers, including other areas, to reach excellence in their respective industries